Absolute fitness / Mohamad Faiz Akmal Mohamad Zaidi, Muhammd Haris Ikhwan Muhammad Hanafi and Ahmad Azfar Shah Ahmad Shukri Shah - Mohamad Zaidi, Mohamad Faiz Akmal; Muhammad Hanafi, Muhammd Haris Ikhwan; Ahmad Shukri Shah, Ahmad Azfar Shah (Faculty of Computer and Mathematical Sciences, 2022)
People nowadays tend to have problems related to their health. In our community we can see people with problems of being overweight, of being very unproductive and leading an unhealthy lifestyle. There are many factors as to why people in this era often face with these kinds of problems. Complications like a packed schedule, lack of equipment, lacking in fitness knowledge and the inability to start a plan are mostly the reason people end up having health problems. Due to these rising issues, we came up with an idea to create an app called Absolute Fitness. Absolute Fitness is an application that has many features which can help users to be physically fit and opting for a healthier lifestyle. The Home Workout, Calorie Counter and Outdoor Activity are the main features of this app. These features could help you to differentiate the types of workout exercise according to the part of the muscle you want to focus on without the need to use exercise equipment. Other than that, it could also count your calorie intake, the rate of your heartbeat, running distances and many others whenever we want the app to. These features are normally found on different kinds of app and are rarely found in only one single app. In conclusion, we created this app to provide an easy access to these features all at the same time, on a single app to maximize the time taken and efficiency to plan a workout schedule and further increase the effectiveness of the muscle growth.¬